Public governance - nowe podejście do zarządzania rozwojem lokalnym - Banachowicz, Beata (Public Governance - New Concept of Management in Local Development Processes, 2007)
The aim of this paper is to present the change from traditional rule-book administration towards public governance in Lodz Region. The paper an investigates innovative approach towards local and regional management which includes following aspects: • governance - relation between government and local society, NGO's, entrepreneurs and other actors at local and regional level, • social capital - the importance of human capital for development of communities, • regional innovation strategy (RIS) - improving competitiveness of regions and communes. The success of this innovative approach demands overcoming number of barriers occurring within implementation processes. It point who is the subject of city and regional management, how should public offices be managed (not administrated), how the process of local and regional management should be organized to improve competitiveness of the region and increase development processes.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1161, s. 613-622